A hybrid cryptography technique for data storage on cloud computing. (18th August 2021) - Bermani, Ali Kadhim; Murshedi, Tariq A. K.; Abod, Zaid A.
Abstract: Cloud computing security has received great attention by researchers in the past few years due to the importance of the data used and the increasing use of cloud computing, which has become the provision of many services and in various fields. So, data Security is a major issue in storing data on clouds. Cryptography techniques are among the most important ways to provide data security on cloud. This paper presents a data protection model where data is encrypted using a hybrid cryptographic algorithm which is composed of Advanced Encryption Standard (AES), Blowfish and Message-Digest algorithm (MD5). Thus, this model provides speed and robust data encryption.